1992
DOI: 10.1557/jmr.1992.1313
|View full text |Cite
|
Sign up to set email alerts
|

Two different low friction mechanisms of diamond-like carbon with silicon coatings formed by plasma-assisted chemical vapor deposition

Abstract: Diamond-like carbon with silicon (DLC-Si) coatings formed by plasma-assisted chemical vapor deposition showed low friction coefficients of the order of 0.01 against steel without a lubricant, not only in dry atmosphere but also in humid atmosphere, where conventional DLC coatings showed higher friction coefficients of 0.1-0.2. DLC-Si coatings with 1 fim thickness deposited on steel were slid against steel using a conventional ball-on-disk type of apparatus to compare with a low friction mechanism of DLC-Si in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 11 publications
4
47
0
1
Order By: Relevance
“…This increased friction for the Si,O,F doped DLC could be indicative of the formation of a mechanically hard tribofilm (37). The Si,O doped DLC does not show the reduced friction that may have been expected when compared to the a-C:H, as seen in dry sliding experiments (3,4). This however is in-line with literature precedents concerning Si-DLCs in lubricated contacts where SiDLCs friction reducing properties are markedly reduced (8,9).…”
Section: Frictionsupporting
confidence: 86%
See 1 more Smart Citation
“…This increased friction for the Si,O,F doped DLC could be indicative of the formation of a mechanically hard tribofilm (37). The Si,O doped DLC does not show the reduced friction that may have been expected when compared to the a-C:H, as seen in dry sliding experiments (3,4). This however is in-line with literature precedents concerning Si-DLCs in lubricated contacts where SiDLCs friction reducing properties are markedly reduced (8,9).…”
Section: Frictionsupporting
confidence: 86%
“…The main mechanism for reduced friction in Si-DLC contacts is identified as being caused by production of SiOx species. These are often referred to as silicon rich oxide debris (2,4,11,38). This debris represents oxidative destruction and removal of Si within the coating which in turn amplifies wear of the DLC as a whole.…”
Section: Proposed Mechanism Of Wear Repressionmentioning
confidence: 99%
“…DLC films are synthesized by ion-or plasma-47 based processes using hydrocarbon precursor gases and 48 therefore contain substantial amounts of hydrogen 49 (usually 10-50 atomic%). Techniques for DLC film 50 deposition include direct ion beam processes, plasma-51 enhanced chemical vapor deposition, and electron 52 cyclotron resonance CVD processes [1,[9][10][11]. DLC films 53 are amorphous with no long-range order, and the car-54 bon is present in both the hybridized sp 3 (diamond) and 55 sp 2 (graphite) bonding configurations, although sp 1 56 (polymeric) configuration has also been observed.…”
mentioning
confidence: 99%
“…The friction coefficient of unlubricated DLC films in dry gases can be as low as 0.01, but this value can reach values as high as 0.10 and 0.20 when measured in a 10% relative humidity [1][2][3]. Various researchers [2][3][4] have shown that conventional DLC films doped with elements such as Si and Ti exhibit low pin-on-disk friction coefficients in humid environments. Amorphous DLC coatings have shown extremely smooth and dense surface morphology.…”
Section: Introductionmentioning
confidence: 99%
“…DLC films containing Si (Si-DLC) exhibit friction coefficients as low as 0.04 [2][3][4] at ambient humidity and temperature and are therefore highly promising for tribological applications. It has been also shown repeatedly that the adhesion of the Si-DLC coating on various substrates, including steel has been excellent [4].…”
Section: Introductionmentioning
confidence: 99%